APPLICATION OF PROGRESSIVE MUSCLE RELAXATION TO REDUCING THE ANXIETY OF HYPERTENSION CLIENTS - Isrianawati, Erny; Rusdianingseh, Rusdianingseh; Hatmanti, Nety Mawarda; Khafid, M. (Nurse and Holistic Care, 2023)
Background: Families with hypertension will cause anxiety or anxiety which can affect the stability of blood pressure. One of the managements of anxiety with psychotherapy methods is by doing progressive muscle relaxation therapy. Progressive Muscle Relaxation to get a feeling of relaxation, so as to reduce anxiety and stress. Objective: The aim of the study was to determine the application of progressive muscle relaxation therapy to reduce anxiety in hypertensive clients. Methods: This research method uses a descriptive method with a case study approach. The instruments used were HARS questionnaire sheets and Progressive Muscle Relaxation SOP sheets. The number of respondents was 1 person with hypertension with an anxiety nursing diagnosis. Result: The results of applying progressive muscle relaxation given 2 times per day for 7 days with a duration of 30-45 minutes each meeting showed a decrease in anxiety level from moderate anxiety to mild anxiety, followed by a decrease in blood pressure. Conclusion: The application of progressive muscle relaxation has proven effective in reducing anxiety in hypertensive clients. This therapy can be used as an adjunct to overcome anxiety which is useful for reducing blood pressure of hypertensive clients.